The Role Of Motivation In Mediating Workload And Discipline On Teacher Performance In Elementary Schools In Tompaso District, Minahasa Regency - Kolibu, Miryam Theofilia; Rawis, Joulanda A. M.; Lengkong, Jefry S. J.; Sumual, Shelty D. M.; Umbase, Ruth (International Journal of Information Technology and Education, 2026)
This study aims to determine the role of motivation in mediating workload and discipline on teacher performance in elementary schools in Tompaso District, Minahasa Regency. The research method used in this study is a quantitative method. The sample in this study was 156 respondents. The data collection technique was a questionnaire structured in several statements and measured using a likert scale. Data were processed using SMART PLS 4.0.9.6. The results of this study indicate: (1) a significant effect of workload on teacher performance, (2) a significant effect of discipline on teacher performance, (3) a significant effect of motivation on teacher performance, (4) a significant effect of workload on motivation, (5) a significant effect of discipline on motivation, (6) a significant effect of workload on teacher performance through motivation, and (7) a significant effect of discipline on teacher performance through motivation.